CO130 Dyspnea and health-related quality of life in patients with persistent symptoms after at least six months of hospital discharge due to COVID-19 (2023)
Objectives. To evaluate dyspnea in patients with persistent symptoms after at least six months of hospital discharge due to COVID-19 and its correlation with the quality of life, fatigue, and functional status. Methods. This cross-sectional study included 101 patients with persistent symptoms after at least six months of hospital discharge for COVID-19. A physician evaluated dyspnea using the Modified Medical Research Council (mMRC) scale questionnaire, the quality of life with the EQ-5D-5L, fatigue with an analog scale (0=no fatigue to 10=worst possible fatigue), and functional status with the Post-COVID-19 Functional Status scale (grade 0=no limitation to grade 4=severe limitation). We used Fisher’s exact test for categorical data and the Wilcoxon rank-sum test for continuous data to assess differences across groups. Spearman’s test was used for correlations. The significance level was 5%. Results. Of the participants, 56.4 % (n=57) were women with a mean age of 57.7 (SD±16.3) years. The most reported symptoms were muscle weakness (61.4%, n=62), dyspnea (51.5%, n=52), muscle pain (49.5%, n=50), and fatigue 41 (40.6%, n=41). Seventy-two (71.3%) participants reported an increase in the mMRC dyspnea scale score, with no differences according to ICU requirements. Forty of the 81 (49.4%) participants with an mMRC grade 0 before COVID-19 reported a grade 3-4 during the medical visit. The EQ5D-5L index was 10% lower after COVID-19 (median difference: -0.01 points, interquartile range: -0.14 to -0.05), and those who required ICU admission had a more significant change in the index than those who did not (-0.12 vs -0.07, p=0.008). The mMRC grade reported during the medical visit was negatively correlated with the EQ5D-5L index (rho=-0.5836716, p<0.0001) and positively correlated with fatigue (rho=0.38,p =0.001) and functional status (rho=0.41,p <0.001). Conclusions. Dyspnea is prevalent among patients discharge for COVID-19 with persistent symptoms and may affect their quality of life and functional status.